White women's long 'work' to freedom : an analysis of the inconsistencies surrounding the inclusion of white women in affirmative action - Venter, Trace Joan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2004.